Significant Advancement in Various Synthetic Strategies and Pharmacotherapy of Piperine Derivatives: A Review - Joshi, Sagar; Salahuddin; Mazumder, Avijit; Kumar, Rajnish; Shabana, Km; Tyagi, Sonakshi; Rana, Kavita; Ahsan, Mohamed J.; Yar, Mohammad Shahar; Arya, Arvind; Khurana, Navneet (Current Topics in Medicinal Chemistry, 2023)
Background: Piperine is a natural compound found in black pepper that has been traditionally used for various therapeutic purposes. In the ayurvedic system of medication there is a lot of evidence which shows that the piperine is widely used for different therapeutic purpose. In recent years, there has been an increasing interest in the pharmacological and therapeutic potential of piperine and its derivatives in modern medicine. In order to increase the bioavailability and therapeutic effectiveness of piperine and its analogs, researchers have been looking at various extraction methods and synthesis approaches. Many studies have been conducted in this area because of the promise of piperine as a natural substitute for synthetic medications. Objectives: The objective of this review article is to provide an up-to-date analysis of the literature on the synthesis of piperine analogs, including their extraction techniques and various biological activities such as antihypertensive, antidiabetic, insecticidal, antimicrobial, and antibiotic effects. Additionally, the review aims to discuss the potential of piperine in modern medicine, given its traditional use in various medicinal systems such as Ayurveda, Siddha, and Unani. The article also provides a comprehensive analysis of the plant from which piperine is derived. Conclusion: This review article provides a thorough examination of piperine and the source plant. The best extraction technique for the extraction of piperine and the synthesis of its analogs with various biological activities, including antihypertensive, antidiabetic, insecticidal, antibacterial, and antibiotic properties, are covered in the article. This review aims to provide an updated analysis of the literature on the synthesis of piperine analogs.
Keywords: Pharmacological